(untitled) (Research, Society and Development, 2021)
This article has as specific purpose to present an analysis of how language works in/on the practice of reading in the classroom and its meaning in the learning of the subject-student from the use of the Portuguese Language textbook entitled "Tecendo Linguagens" - PNLD (2017-2019) - used in the 9th grade of elementary school in a riverside school located on Pacuí Island, in the city of Cametá, Pará. Methodologically, we conducted a qualitative and discourse analytical research, using the theoretical and methodological devices of Discourse Analysis. Affiliated to a discursive perspective, we analyzed the elements of presentation (summary and cover) and the construction of the set of images of the textbook; material that provided important discursive evidence so that we could bring in the construction of the narrative of this text, the urgent need to think about new ways of reading, of practicing reading in the school space, beyond the textbook and a capitalist project, urbanized that is totally distant from the reality of the subject-student who lives in the Amazônia Tocantina